(untitled) (Research, Society and Development, 2022)
Chlamydia trachomatis infection is the most prevalent bacterial Sexually Transmitted Infection (STI) worldwide. They can be asymptomatic in up to 80% of cases and lead to Pelvic Inflammatory Disease, infertility and ectopic pregnancy in a young female population. The aim of this study was to estimate the prevalence of C. trachomatis infection in endocervical samples of students from a public university in the state of Pará, and to verify the social, behavioral and associated gynecological complaints characteristics. It is a prospective cross-sectional study involving 127 female students at a public university in Belém, in the state of Pará, between October 2018 and December 2019. Endocervical samples were obtained during the cervical cancer screening. DNA extraction was performed by adapting the protocol of the “GE Healthcare illustra™ blood genomicPrep Mini Spin Kit” Kit. A 270bp amplification of the human β-globin gene was performed for quality control of the extraction. For the detection of C. trachomatis, the nested-PCR Polymerase Chain Reaction (PCR) was used to amplify 327bp of the ompA gene. The overall prevalence was 10.2%. There was a significant association in the lack of condom use during sexual intercourse (p=0.02); and not performing the PCCU annually (p=0.05). The high prevalence of this infection may be a consequence of the lack of condom use and the lack of periodicity in the gynecological examination. National studies are necessary to understand the epidemiology of this infection and to build public policies aimed at gynecological health.